An Unprecedented Pseudo‐[3+2] Annulation between N‐(4‐Methoxyphenyl)aldimines and Aqueous Glutaraldehyde: Direct Synthesis of Pyrrole‐2, 4‐dialdehydes. Issue 24 (29th May 2017) - Ramaraju, Panduga; Mir, Nisar A.; Singh, Deepika; Sharma, Preetika; Kant, Rajni; Kumar, Indresh
Abstract : A new method for the direct one‐pot synthesis of substituted pyrrole‐2, 4‐dialdehdyes was developed. This overall pseudo‐[3+2]‐annulation reaction between glutaraldehyde and N ‐(4‐methoxyphenyl)aldimines proceeds through proline‐catalyzed direct Mannich reaction/cyclization, followed by 2‐iodoxybenzoic acid mediated oxidative rearrangement of the in situ generated intermediate to give pyrrole‐2, 4‐dialdehydes in high yields (up to 80 %). Abstract : The 2‐iodoxybenzoic acid (IBX)‐mediated oxidative rearrangement of tetrahydropyridine intermediates, prepared through proline‐catalyzed annulation between glutaraldehyde and imines, is explored as a means for the regioselective synthesis of pyrrole‐2, 4‐dialdehydes. PMP = 4‐MeOC6 H4 .